2013
DOI: 10.3390/rs6010310
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Comparison of Vegetation Indices Derived from Landsat-7 Enhanced Thematic Mapper Plus (ETM+) and Landsat-8 Operational Land Imager (OLI) Sensors

Abstract: Landsat-7 Enhanced Thematic Mapper Plus (ETM+) and Landsat-8 Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS) are currently operational for routine Earth observation. There are substantial differences between instruments onboard both satellites. The enhancements achieved with Landsat-8 refer to the scanning technology (replacing of whisk-broom scanners with two separate push-broom OLI and TIRS scanners), an extended number of spectral bands (two additional bands provided) and narrower bandwidth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(158 citation statements)
references
References 36 publications
6
146
0
6
Order By: Relevance
“…WV-2 and QB satellite images were purchased from the ArcDATA Company (Table 2). For atmospheric correction, the Fast Line-of-sight Atmospheric Analysis of Hypercubes was used (Dominguez et al, 2015;Li et al, 2014). All image pre-processing was implemented with ENVI SW (ENVI; version 5.3, Excelis, Inc., McLean, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…WV-2 and QB satellite images were purchased from the ArcDATA Company (Table 2). For atmospheric correction, the Fast Line-of-sight Atmospheric Analysis of Hypercubes was used (Dominguez et al, 2015;Li et al, 2014). All image pre-processing was implemented with ENVI SW (ENVI; version 5.3, Excelis, Inc., McLean, VA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to study continuity among sensors from the same series of satellites by considering of the important parameters including sensor characteristics, over-pass time, scanning system, angular affect and etc. A few studies related to the continuity of Landsat 8 have been conducted, including preflight and post-launch calibrations [28][29][30][31][32][33]. Most of these studies have shown that the continuity between the Landsat-8 OLI and Landsat-7 ETM+ is good.…”
Section: Introductionmentioning
confidence: 99%
“…Markham conducted a pre-launch and on-orbit radiometric characterization and calibration of Landsat 8 and found that the uncertainty of radiance calibration performance was within 2%, while for the reflectance calibration it was within 3% [29]. Li compared the consistency of four spectral indices for four land cover types in southeast Asia and found the correlation coefficients (R 2 ) to be a maximum of 0.96 for measurements over a two-day period [33]. However, few comparison of the continuity of various VIs for Landsat series data has been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Un ulteriore strato informativo derivato da OT è costituito dal dato Landsat 8 (L8) OLI, che è stato utilizzato per il calcolo dell'indice NDVI (Normalized Difference Vegetation Index - Li et al 2013).…”
Section: Dati Derivati Da Telerilevamentounclassified